Fast and Accurate Spelling Correction Using Trie and Damerau-levenshtein Distance Bigram - Viny Christanti M.; Rudy Rudy; Dali S. Naga (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This research was intended to create a fast and accurate spelling correction system with the ability to handle both kind of spelling errors, non-word and real word errors. Existing spelling correction system was analyzed and was then applied some modifications to improve its accuracy and speed. The proposed spelling correction system is then built based on the method and intuition used by existing system along with the modifications made in previous step. The result is a various spelling correction system using different methods. Best result is achieved by the system that uses bigram with Trie and Damerau-Levenshtein distance with the word level accuracy of 84.62% and an average processing speed of 18.89 ms per sentence.